2015
DOI: 10.1039/c5ra11826c
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical and thermal properties of graphene oxide/ultrahigh molecular weight polyethylene nanocomposites

Abstract: Graphene oxide (GO) was prepared according to a modified Hummers method, and a range of GO/ultrahigh molecular weight polyethylene (UHMWPE) composites were fabricated then their mechanical and thermal properties were investigated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
69
1
4

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 96 publications
(79 citation statements)
references
References 34 publications
5
69
1
4
Order By: Relevance
“…. Also the microhardness attained in the current research (6.83 HV) is quite higher than the maximum (6.5 and 5 HV) obtained in previous research that used GO of equal amount to reinforce UHMWPE , respectively. The increase in hardness of all the GNPs reinforced UHMWPE composites over the pure matrix is due to the 2D nature of GNPs that enhances strong interfacial bond between the matrix and the reinforcement allowing efficient load transfer mechanism.…”
Section: Resultscontrasting
confidence: 81%
See 1 more Smart Citation
“…. Also the microhardness attained in the current research (6.83 HV) is quite higher than the maximum (6.5 and 5 HV) obtained in previous research that used GO of equal amount to reinforce UHMWPE , respectively. The increase in hardness of all the GNPs reinforced UHMWPE composites over the pure matrix is due to the 2D nature of GNPs that enhances strong interfacial bond between the matrix and the reinforcement allowing efficient load transfer mechanism.…”
Section: Resultscontrasting
confidence: 81%
“…Also, hot pressing with carefully selected set of parameters can pave the way for the mass production of high quality UHMWPE nanocomposites. A comprehensive review has shown that several studies have been carried out on the behavior of UHMWPE‐graphene composite in terms of physical, mechanical, thermal, electrical, and biocompatible properties . However, very few studies have investigated the possible application of UHMWPE with graphene in the field of mechanical bearings .…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, a challenging task for this field is fabrication of UHMWPE nanocomposites with uniformly dispersed fillers . Polyolefin nanocomposites can be conceptually fabricated by solution compounding, melt blending, and in situ polymerization . However, UHMWPE, due to a lack of flowability and an appropriate solvent, can be produced by two former methods.…”
Section: Introductionmentioning
confidence: 99%
“…Figure shows the storage modulus, loss modulus, and glass‐transition temperature for the tested materials; they were obtained from the dynamic mechanical analysis patterns. The storage modulus presented in Figure (a) shows that the neat and filled composites exhibited a decrease in the rubbery plateau level up to temperatures approaching 250 °C; this was related to the degradation of PR . The storage modulus of the ag‐C 3 N 4 ‐filled composite was significantly higher than those of the neat and GO‐filled composites and could be maintained above 250 °C.…”
Section: Resultsmentioning
confidence: 99%